Redefining “Primary Needs” Through Humanistic-Theocentric Approach. - Septyan, Krisno (International Journal of Islamic Khazanah, 2025)
This study seeks to raise awareness about the definition of primary needs based on the ultimate purpose of human existence. The approach adopted in this research is humanistic-theocentric. Society has become deeply immersed in Maslow's theory of needs, particularly regarding primary needs, to the extent of neglecting the true priorities aligned with the purpose of human creation. Maslow's theory is critiqued for the inherent biases in the science it represents. Secularism is identified as the root problem, where modern science has overlooked a fundamental element of knowledge—God—and, consequently, the essence of human creation. People are preoccupied with fulfilling their needs solely for the purpose of meeting basic necessities. Ultimately, this study identifies a hierarchy of consumption where eating food and purchasing a house are not considered primary needs. Instead, the primary needs of humans are worship, sharing prosperity, and learning to know God (ma’rifatullah).